2019
DOI: 10.1038/s41598-019-54958-6
|View full text |Cite
|
Sign up to set email alerts
|

Experience-dependent development of visual sensitivity in larval zebrafish

Abstract: The zebrafish (Danio rerio) is a popular vertebrate model for studying visual development, especially at the larval stage. For many vertebrates, post-natal visual experience is essential to fine-tune visual development, but it is unknown how experience shapes larval zebrafish vision. Zebrafish swim with a moving texture; in the wild, this innate optomotor response (OMR) stabilises larvae in moving water, but it can be exploited in the laboratory to assess zebrafish visual function. Here, we compared spatial-fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 58 publications
1
14
0
Order By: Relevance
“…Experiments in humans and mammalian models are, however, constrained by the limitations described in the introduction. CPs have therefore been identified and interrogated in a number of models more conducive to experimentation: Danio rario ( Riley et al, 1997 ; Moorman et al, 2002 ; Avitan et al, 2017 ; Xie et al, 2019 ); H. americanus ( Govind and Pearce, 1989 ); C. elegans ( Swanson and Riddle, 1981 ), and Drosophila ( Fushiki et al, 2013 ; Marley and Baines, 2011 ; Giachello and Baines, 2015 ). The identification of CPs in the fruit fly means that the A27h-related larval locomotor circuit provides an exciting opportunity to provide network, cellular and mechanism-level resolution insight into the role of CPs in neurodevelopment.…”
Section: Using the A27h-related Larval Locomotor Circuit To Model Critical Periods Of Neural Developmentmentioning
confidence: 99%
“…Experiments in humans and mammalian models are, however, constrained by the limitations described in the introduction. CPs have therefore been identified and interrogated in a number of models more conducive to experimentation: Danio rario ( Riley et al, 1997 ; Moorman et al, 2002 ; Avitan et al, 2017 ; Xie et al, 2019 ); H. americanus ( Govind and Pearce, 1989 ); C. elegans ( Swanson and Riddle, 1981 ), and Drosophila ( Fushiki et al, 2013 ; Marley and Baines, 2011 ; Giachello and Baines, 2015 ). The identification of CPs in the fruit fly means that the A27h-related larval locomotor circuit provides an exciting opportunity to provide network, cellular and mechanism-level resolution insight into the role of CPs in neurodevelopment.…”
Section: Using the A27h-related Larval Locomotor Circuit To Model Critical Periods Of Neural Developmentmentioning
confidence: 99%
“…114 Using OMR, it was recently demonstrated for zebrafish, as has been shown for mouse, 123 that dynamic visual experience is required for the proper stratification of retinal layers in early eye maturation. 124 Studies have shown that the OMR displayed by larval zebrafish is lost around 16 dpf and that adult zebrafish rely mainly on mechanosensory stimuli via the lateral line for sensing movement, and on positive rheotaxis (defined as the tendency to turn to face into an oncoming current) for maintaining position in flowing water. 125 Larval zebrafish also display positive rheotaxis.…”
Section: Functional Vision Testingmentioning
confidence: 99%
“…The OMR apparatus was adapted from one previously described (Supplementary Figure S2) [21,22]. Figure S2a).…”
Section: Optomotor Response (Omr) (A) Apparatus and Proceduresmentioning
confidence: 99%